Challenge studies in chickens to evaluate the efficacy of commercial Newcastle disease vaccines against the strains of Newcastle disease virus prevalent in South Africa since 2002 - Bisschop, Shahn P.R. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2009.